2019
DOI: 10.1016/j.cjtee.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Parkland formula in the estimation of resuscitation fluid volume in adult thermal burns

Abstract: Purpose Acute burn resuscitation in initial 24 h remains a challenge to plastic surgeons. Though various formulae for fluid infusion are available but consensus is still lacking, resulting in under resuscitation or over resuscitation. Parkland formula is widely used but recently its adequacy is questioned in studies. This study was conducted to see how closely the actual volume of fluid given in our center matches with that of calculated volume by Parkland formula. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…Neither was a more accurate formula found for burn injuries ranging up to 60% TBSA [ 3 ] nor has any other formula gained the same popularity as the Parkland formula still has [ 6 , 7 ]. In a recent study with 90 burn patients by Ete et al [ 5 ], the necessary resuscitation volume was 3.14 mL/kg/% TBSA and 3.36 mL/kg/%TBSA for burn patients with concomitant inhalational injury and, therefore, close to the 3.5 mL/kg/%TBSA of the original Parkland formula.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Neither was a more accurate formula found for burn injuries ranging up to 60% TBSA [ 3 ] nor has any other formula gained the same popularity as the Parkland formula still has [ 6 , 7 ]. In a recent study with 90 burn patients by Ete et al [ 5 ], the necessary resuscitation volume was 3.14 mL/kg/% TBSA and 3.36 mL/kg/%TBSA for burn patients with concomitant inhalational injury and, therefore, close to the 3.5 mL/kg/%TBSA of the original Parkland formula.…”
Section: Introductionmentioning
confidence: 87%
“…Apart from the Parkland formula, many other formulas have been proposed to estimate the necessary resuscitation volume more closely, e.g., Evans formula [ 2 ] or the modified Brooke formula (2 mL/kg/%TBSA) [ 3 ]. Those formulas as well as the Parkland formula have been tested in various studies [ 4 , 5 ]. Neither was a more accurate formula found for burn injuries ranging up to 60% TBSA [ 3 ] nor has any other formula gained the same popularity as the Parkland formula still has [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the Parkland formula is utilised, the volume of fluid has to be adjusted according to the urinary output and other parameters leading to considerable variations in the fluid administered. A study by Ete et al has shown significant differences in the fluid administered based on urine output and the fluid calculated by Parkland formula [7]. The imprecise body surface area calculations and variations in fluid shift may contribute to this discrepancy.…”
Section: Fluid Resuscitation In Severe Burnsmentioning
confidence: 99%
“…Various resuscitation formulae are accessible at the request of the burn care provider. Despite many important advances in the fluid management field, smooth resuscitation is not ensured by any method [38]. The Parkland formula is accepted worldwide and it is the consensus formula currently [32].…”
Section: Fluid Resuscitationmentioning
confidence: 99%